Follow-up of humoral and cellular immune responses after the third SARS-CoV-2 vaccine dose in multiple myeloma patients - Raimondi, Vincenzo; Storti, Paola; Vescovini, Rosanna; Franceschi, Valentina; Toscani, Denise; Notarfranchi, Laura; Dalla Palma, Anna Benedetta; Iannozzi, Nicolas Thomas; Minesso, Sergio; Scita, Matteo; Lungu, Oxana; Dessena, Mattia; et al. (Frontiers in Immunology, 2025)
The stability of immune responses to SARS-CoV-2 vaccines, especially concerning the cross-reactive recognition of the Omicron variant, remains incompletely characterized in multiple myeloma (MM) patients. This study evaluated humoral responses in 29 MM patients and cellular responses in a subset of 19 MM patients, specific to Wuhan and Omicron spike proteins, between 16 and 26 weeks following the third vaccine dose. After 26 weeks, we highlighted a significant reduction in the neutralizing antibodies to both spikes and the percentages of IFN-γ+CD107a+ spike-specific CD8+ T cells. On the other hand, patients who underwent an additional stimulation between the two time points, through either a fourth vaccine dose or breakthrough infection, showed a significant increase in neutralizing antibodies and stable levels of cytotoxic CD8+ T cells. Additionally, those with only three doses experienced a higher rate of breakthrough infections during the 32-week follow-up period. These findings underscore the waning of vaccine-induced immunity over time and may help benefit-risk evaluation in vaccination strategies in MM patients.